Screening sugarcane somaclones and their parent varieties against red rot (Colletotrichum falcatum) and assessment of Variability by RAPD and SSR markers (SAARC Journal of Agriculture, 2016)
The experiment was conducted to find out red rot disease causing pathogenic reactions of somaclones (R0) and their respective parents at BSRI farm in the cropping season 2011-2012. A total number of sugarcane genotypes 24 including 4 sugarcane varieties viz. Isd 37, Isd 38, Isd 39 and also Isd 40 were inoculated to screen red rot resistant levels (R = Resistant, MR = Moderately Resistant) to susceptible levels (S = Susceptible, MS = Moderately Susceptible, HS = Highly Susceptible) after 7 months of planting. As a result, Isd 37 variety (source/parent) and its somaclones CC3712 and CC3786 were found to be resistant while 7 somaclones showed moderately resistant reaction. Furthermore, somaclones of Isd 38 variety viz. CC382 as moderately resistant, CC3810 as moderately susceptible and also CC11(38)8 as susceptible reaction were recorded while Isd 38 variety showed resistant reaction. On the other hand, Isd 39 and Isd 40 source varieties with their somaclones were found as resistant reaction against red rot pathogen. Some somaclones showed different reaction from their source varieties such as moderately resistant somaclones were obtained from resistant source variety Isd 37 while somaclones CC382 as moderately resistant, CC3810 as moderately susceptible and somaclone CC388 as susceptible were obtained from resistant source variety Isd 38 against red rot pathogens respectively. Besides, some somaclones showed similar reaction from their resistant source varieties Isd 37, Isd 39 and also Isd 40. It revealed that reaction against red rot pathogen, induced somaclones showed variation with their source varieties. Red rot resistance somaclones were isolated and assessed for the presence of variability through RAPD and SSR markers. Cluster and sub cluster formation verified the presence of variability in the red rot resistance somaclones with respect to the parent.SAARC J. Agri., 13(2): 173-182 (2015)